2010
DOI: 10.1007/s10404-010-0743-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical conditions and breakup of non-squashed microconfined droplets: effects of fluid viscoelasticity

Abstract: Droplet breakup in systems with either a viscoelastic matrix or a viscoelastic droplet is studied microscopically in bulk and confined shear flow, using a parallel plate counter rotating shear flow cell. The ratio of droplet diameter to gap spacing is systematically varied between 0.1 and 0.85. In bulk shear flow, the effects of matrix and droplet viscoelasticity on the critical capillary number for breakup are very moderate under the studied conditions. However, in confined conditions a profoundly different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The effect is larger in presence of a larger confinement ratio. In particular, in agreement with some recent experiments [31], we have found that the formation of multiple neckings, which is acknowledged as a distinctive feature of confined break-up [11,14], is also affected by the presence of viscoelasticity: it visibly changes as soon as the ratio of fluid relaxation time to droplet emulsion time (i.e. the Deborah number) becomes of the order of 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect is larger in presence of a larger confinement ratio. In particular, in agreement with some recent experiments [31], we have found that the formation of multiple neckings, which is acknowledged as a distinctive feature of confined break-up [11,14], is also affected by the presence of viscoelasticity: it visibly changes as soon as the ratio of fluid relaxation time to droplet emulsion time (i.e. the Deborah number) becomes of the order of 1.…”
Section: Discussionsupporting
confidence: 92%
“…3-7. First, it is evident that viscoelasticity has a stabilizing effect on droplet break-up [16][17][18][19][20][21][22][23][24][25], with a larger effect in presence of a larger confinement ratio [31]. Second, the formation of multiple neckings -a distinctive feature of break-up of confined droplets -is also affected by the presence of viscoelasticity.…”
Section: Effects Of Droplet Viscoelasticity On Critical Capillarymentioning
confidence: 99%
“…The two mechanisms can be distinguished because the equilibrium mechanism leads to binary droplet breakup with two daughter droplets whereas the transient mechanism via threads formation is characterized by multiple droplet breakup into smaller droplets. [20a,23] The dynamics of droplet breakup is further influenced by the presence of surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…For viscosity ratios below one, confinement suppresses breakup, whereas for viscosity ratios above one, breakup is promoted by confinement [Vananroye et al (2006)]. Furthermore, Cardinaels and Moldenaers (2011) studied the combined effect of confinement and viscoelasticity of one of the components. They found that droplet breakup in confined shear flow is also strongly dependent on the viscoelasticity of the components.…”
Section: Introductionmentioning
confidence: 99%
“…They found that droplet breakup in confined shear flow is also strongly dependent on the viscoelasticity of the components. More specifically, in confinement matrix viscoelasticity causes breakup at much lower critical Ca numbers as compared to that for droplets in a Newtonian matrix, whereas the viscoelastic effects in bulk conditions were limited [Cardinaels and Moldenaers (2011)]. …”
Section: Introductionmentioning
confidence: 99%